2018
DOI: 10.1021/acs.jpcc.8b00434
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocapacitive Energy Storage in Schiff Base Polymer with Salphen-Type Ligands

Abstract: Salphen-type nickel Schiff bases Ni(salphen), Ni(CH 3 -salphen), and Ni(CH 3 O-salphen) are synthesized and electropolymerized on stable ITO electrode, respectively. The morphologies of the three polymer electrodes were evaluated by field emission scanning electron microscopy (FESEM). X-ray photoelectron spectroscopy (XPS) measurements were carried out to shed light on the polymerization mode and energy storage mechanism. Meanwhile, kinetic analysis of the redox reactions was used to verify the pseudocapacitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The energy‐dispersive X‐ray spectroscopy (EDX) spectra of the products revealed the incorporation of both cobalt and nickel ions within the products as metal nodes, as evidenced by the detection of both cobalt and nickel, in addition to carbon and oxygen originating from the organic building blocks (Figure c and Figure S2, Supporting Information). The high‐resolution X‐ray photoelectron spectroscopy (XPS) data of Co x Ni y ‐CATs (Figure e,f) for Co 2p and Ni 2p confirmed the presence of divalent Co 2+ and Ni 2+ , as evidenced by a Co 2p3/2 peak at 780.7 eV and a Ni 2p3/2 peak at 855.5 eV, respectively. Moreover, the ratios between Co 2+ and Ni 2+ within the five samples of Co x Ni y ‐CATs were determined to be ≈49:51, 41:59, 32:68, 27:73, and 15:85, as measured from the EDX spectra (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
“…The energy‐dispersive X‐ray spectroscopy (EDX) spectra of the products revealed the incorporation of both cobalt and nickel ions within the products as metal nodes, as evidenced by the detection of both cobalt and nickel, in addition to carbon and oxygen originating from the organic building blocks (Figure c and Figure S2, Supporting Information). The high‐resolution X‐ray photoelectron spectroscopy (XPS) data of Co x Ni y ‐CATs (Figure e,f) for Co 2p and Ni 2p confirmed the presence of divalent Co 2+ and Ni 2+ , as evidenced by a Co 2p3/2 peak at 780.7 eV and a Ni 2p3/2 peak at 855.5 eV, respectively. Moreover, the ratios between Co 2+ and Ni 2+ within the five samples of Co x Ni y ‐CATs were determined to be ≈49:51, 41:59, 32:68, 27:73, and 15:85, as measured from the EDX spectra (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 74%
“…To look into the relative contributions of Faradic and capacitive processes to the total capacity, we used cyclic voltammetry following a method that has been previously reported for studies of pyrites in Li/Na-ion battery chemistries (details shown in the Supporting Information). From this analysis, the ratio between capacities coming from capacitive and Faradic processes was determined to be 0.23:1. The total capacity is therefore found to be 203 mAh/g, of which 165 mAh/g is Faradic in nature and 38 mAh/g is capacitive.…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric bis(salicilydenimine) complexes of transition metals (MSalens) represent a class of conductive polymers with distinct properties. Specifically, polymeric Salen complexes based on nickel have a large reversible electroactivity window, perfectly matching the TEMPO/TEMPO + redox potential (anodic limit of electroactivity reaches 4.3 V vs Li/Li + ), [15] and a conductivity up to 100 S cm −1 , [16] while their specific redox capacitance and energy density (ca. 330 J g −1 ) [17] exceed those of most conductive polymers.…”
Section: Introductionmentioning
confidence: 96%